Effect of different soaking conditions on the quality of tartary buckwheat wine - BAI Jia-jia; JI De-rong; HE Yu-zhen; ZHONG Qiu; DUAN Li-li (Shipin yu jixie, 2023)
Objective: This study aimed to find the most appropriate tartary buckwheat variety for soaking wine. Methods: The contents of total flavones, soluble solids, total phenols, antioxidant properties, color difference and light transmittance of three kinds of tartary buckwheat wines (A, B and C) were investigated. The effects of different tartary buckwheat varieties on wine quality characteristics were explored. Results: The contents of total flavone, total phenol, soluble solid and the scavenging rate of DPPH and ABTS free radicals of tartary buckwheat B were the highest. The color difference showed that the content of total flavonoids and total phenols had a significant correlation with the color of wine samples. 49 kinds of volatile substances were found in B1 samples after soaking for 40 days, the relative content was 79.488%, among which 16 kinds of esters (the relative content was 49.916%) were the main volatile substances. Conclusion: The variety The variety of tartary buckwheat influences the quality of the wine significantly. The content of flavonoids and total phenols in the wine has a significant correlation with the color of the wine sample. The optimum variety for black wine is tartary buckwheat B.